A novel semi-automated direct lysis method for DNA recovery from live and spent 9mm ammunition. Issue 1 (December 2019) - Subhani, Zuhaib; Coleman, Kiera; Moore, David; Clayton, Tim; Brown, Melanie K.
Abstract: Recovery of cellular material and DNA from ammunition is a potentially valuable process capable of providing probative evidence of criminal use of firearms. However, DNA profiling success rates on ammunition are low, and consequently much of the ammunition recovered from crime scenes is never submitted for DNA analysis. There is also a common assumption that DNA from fired ammunition is likely to have deteriorated following discharge. In this study, DNA recovery and subsequent STR profiling was conducted on live and spent 9mm ammunition, handled by known donors prior to loading. Two methods were compared; the commonly-used double swabbing technique and a novel semi-automated direct lysis method using AutoLys tubes (Hamilton). The direct lysis method involves placing 9mm cartridges into an AutoLys tube and submerging the cartridge in lysis buffer prior to purification. Lysate was recovered by centrifugation facilitated by the AutoLys tube design. It was found that the direct lysis method recovered significantly more DNA and yielded correspondingly improved STR profiles than the double swabbing technique. It was also shown that DNA could be recovered and profiled using the direct lysis method on both live and spent 9mm cartridges. These results demonstrate that DNA suitable for STR analysis can be recovered from spent ammunition with only slightly reduced yields compared to live ammunition. In many cases the last handler of the ammunition was a major contributor to the recovered DNA. It was also found that the ammunition subjected to the direct lysis method did not have any effects on the ballistic markings imparted on the cartridge during the firing process. This shows the compatibility of the direct lysis method with other traditional ammunition examinations.